Step
*
1
of Lemma
Minkowski-equality
1. n : ℕ
2. x : ℝ^n
3. y : ℝ^n
4. r0 < ||y||
5. ||x + y|| = (||x|| + ||y||)
6. r0 < ||y||^2
7. ||x + y||^2 = (||x||^2 + ||y||^2 + (r(2) * x⋅y))
⊢ ∃t:ℝ. ((r0 ≤ t) ∧ req-vec(n;x;t*y) ∧ ((r0 < ||x||) 
⇒ (r0 < t)))
BY
{ ((RWO "-3" (-1) THENA Auto)
   THEN (RWO "rnexp2" (-1) THENA Auto)
   THEN nRAdd ⌜-((||x|| * ||x||) + (||y|| * ||y||))⌝ (-1)⋅) }
1
1. n : ℕ
2. x : ℝ^n
3. y : ℝ^n
4. r0 < ||y||
5. ||x + y|| = (||x|| + ||y||)
6. r0 < ||y||^2
7. (r(2) * ||x|| * ||y||) = (r(2) * x⋅y)
⊢ ∃t:ℝ. ((r0 ≤ t) ∧ req-vec(n;x;t*y) ∧ ((r0 < ||x||) 
⇒ (r0 < t)))
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  x  :  \mBbbR{}\^{}n
3.  y  :  \mBbbR{}\^{}n
4.  r0  <  ||y||
5.  ||x  +  y||  =  (||x||  +  ||y||)
6.  r0  <  ||y||\^{}2
7.  ||x  +  y||\^{}2  =  (||x||\^{}2  +  ||y||\^{}2  +  (r(2)  *  x\mcdot{}y))
\mvdash{}  \mexists{}t:\mBbbR{}.  ((r0  \mleq{}  t)  \mwedge{}  req-vec(n;x;t*y)  \mwedge{}  ((r0  <  ||x||)  {}\mRightarrow{}  (r0  <  t)))
By
Latex:
((RWO  "-3"  (-1)  THENA  Auto)
  THEN  (RWO  "rnexp2"  (-1)  THENA  Auto)
  THEN  nRAdd  \mkleeneopen{}-((||x||  *  ||x||)  +  (||y||  *  ||y||))\mkleeneclose{}  (-1)\mcdot{})
Home
Index